Artificial Intelligence in Education: Transforming Teaching, Learning, and Equity in the 21st Century - Davendra Sharma (International Journal of Social Sciences, Language and Linguistics, 2025)
Artificial intelligence (AI) is reshaping education by transforming the ways teaching and learning are designed, delivered, and experienced in the 21st century. AI-powered technologies enable personalized learning pathways, automate routine administrative tasks, and provide data-driven insights that inform pedagogical decisions (Luckin et al., 2016; Holmes et al., 2022). These innovations allow educators to shift from traditional knowledge transmission toward more student-centred, inquiry-based, and collaborative models of learning. Furthermore, AI offers opportunities to enhance inclusivity and equity by supporting multilingual learners, students with disabilities, and those in geographically remote or underserved contexts (UNESCO, 2021). However, challenges remain, particularly in addressing ethical concerns, algorithmic bias, data privacy, and the digital divide, which disproportionately affects learners in developing regions such as the Pacific (Selwyn, 2019). For AI to serve as a catalyst for equitable and sustainable educational transformation, policies and practices must prioritize human values, cultural contexts, and teacher capacity-building. This paper critically examines the opportunities and challenges of AI in education, emphasizing its implications for equity, pedagogy, and the future of learning in the 21st century.